Echocardiographic evaluation of left ventricular mechanics in sarcoidosis patients without overt heart disease: a systematic review and meta-analysis - Sonaglioni, Andrea; Fagiani, Valeria; Rigoni, Marta; Nicolosi, Gian Luigi; Lucidi, Alessandro; Caminati, Antonella; Lombardo, Michele; Harari, Sergio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: During the last decade, a small number of studies have used speckle tracking echocardiography (STE) to investigate sarcoidosis effect on left ventricular (LV) mechanics in patients without overt heart disease. The present systematic review and meta-analysis has been primarily designed to summarize the main findings of these studies and to examine the overall influence of sarcoidosis on LV-global longitudinal strain (GLS) and left ventricular ejection fraction (LVEF). Methods: All echocardiographic studies assessing conventional echoDoppler parameters and myocardial strain indices in patients with extracardiac sarcoidosis (ECS) vs. healthy controls, selected from PubMed and EMBASE databases, were included. The risk of bias was assessed by using the National Institutes of Health (NIH) Quality Assessment of Case-Control Studies. Continuous data (LV-GLS and LVEF) were pooled as a standardized mean difference (SMD) comparing sarcoidosis group with healthy controls. The overall SMDs of LV-GLS and LVEF were calculated using the random-effect model. Results: The full-text of 13 studies with 785 ECS patients and 567 healthy controls were analyzed. Both average LVEF (60.5±6.6 vs 63.0±4.8%, P<0.001) and LV-GLS (-17.4±3.3 vs -21.0±2.7%, P<0.001) were significantly lower in ECS patients than controls. However, sarcoidosis showed a significantly larger effect on LV-GLS (SMD: -1.26, 95%CI -1.61,-0.91, P<0.001) rather than on LVEF (SMD: -0.51, 95%CI -0.83,-0.20, P=0.001). Substantial heterogeneity was found for the studies that assessed LV-GLS (I2=86.4%) and LVEF (I2=85.3%). Egger’s test gave a P-value of 0.24 for LV-GLS and 0.32 for LVEF assessment, indicating no publication bias. On meta-regression analysis, none of the moderators was significantly associated with effect modification for both LV-GLS and LVEF (all P <0.05). Conclusions: In patients without overt heart disease, the effect of sarcoidosis on LV-GLS is significantly greater than on LVEF. STE analysis should be implemented in clinical practice for the early detection of myocardial involvement in ECS patients.